2021
DOI: 10.3390/plants10071409
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protein Isolation and Label-Free Quantitative Proteomic Analysis in Four Different Tissues of Korean Ginseng

Abstract: Korean ginseng is one of the most valuable medicinal plants worldwide. However, our understanding of ginseng proteomics is largely limited due to difficulties in the extraction and resolution of ginseng proteins because of the presence of natural contaminants such as polysaccharides, phenols, and glycosides. Here, we compared four different protein extraction methods, namely, TCA/acetone, TCA/acetone–MeOH/chloroform, phenol–TCA/acetone, and phenol–MeOH/chloroform methods. The TCA/acetone–MeOH/chloroform method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The total leaf proteins were isolated, as previously reported [ 65 ]. Briefly, 1 g of fine ground ginseng leaf powder was homogenized with 5 mL of ice-cold Tris-Mg/NP-40 extraction buffer (0.5 M Tris–HCl, pH 8.3; 2% ( v / v ) Nonidet P-40 (NP-40); 20 mM MgCl 2 ; 0.07% ( v / v ) β –mercaptoethanol) and centrifuged at 12,000 rpm for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total leaf proteins were isolated, as previously reported [ 65 ]. Briefly, 1 g of fine ground ginseng leaf powder was homogenized with 5 mL of ice-cold Tris-Mg/NP-40 extraction buffer (0.5 M Tris–HCl, pH 8.3; 2% ( v / v ) Nonidet P-40 (NP-40); 20 mM MgCl 2 ; 0.07% ( v / v ) β –mercaptoethanol) and centrifuged at 12,000 rpm for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…After alkylation, the trypsin solution, dissolved in 50 mM TEAB containing 5% acetonitrile (ACN) (enzyme to substrate ratio ( w / w ) of 1:50), was added and incubated at 37 °C overnight. The concentration of obtained peptides was measured using the Pierce Quantitative Fluorometric Peptide Assay kit (Thermo Scientific, Waltham, MA, USA), according to the manufacturer’s instructions [ 65 ]. The digested peptides were subsequently applied to desalting HLB OASIS columns and basic pH reversed-phase (BPRP) fractionation using an in-house developed stage tip, respectively, as reported elsewhere [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the differentially expressed proteins between leaves and rhizomes of soft windflower (Anemone flaccida), most proteins involved in the metabolic pathway of triterpenoid saponins biosynthesis were upregulated in rhizomes (Zhan et al, 2016). Comparative proteome analysis of the leaves, roots, shoots and fruits of Korean Ginseng by label-free quantitative proteomics identified that 67 out of 1,179 differentially regulated proteins were associated with ginsenoside biosynthesis pathways, including MEP pathway, MVA pathway, UDP-glycosyltransferase and oxidoreductase (Van Nguyen et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Among the differentially expressed proteins between leaves and rhizomes of soft windflower ( Anemone flaccida ), most proteins involved in the metabolic pathway of triterpenoid saponins biosynthesis were upregulated in rhizomes ( Zhan et al., 2016 ). Comparative proteome analysis of the leaves, roots, shoots and fruits of Korean Ginseng by label-free quantitative proteomics identified that 67 out of 1,179 differentially regulated proteins were associated with ginsenoside biosynthesis pathways, including MEP pathway, MVA pathway, UDP-glycosyltransferase and oxidoreductase ( Van Nguyen et al., 2021 ).…”
Section: Proteomic Dissection Of Medicinal Plants In Different Manner...mentioning
confidence: 99%